MEMAHAMI “BETAWI” DALAM KONTEKS CAGAR BUDAYA CONDET DAN SETU BABAKAN - Windarsih, Ana (P2KK LIPI, 2013)
To know “Betawi” is interesting, but complex, as researchers and observers view “Betawi” according to their scientific background. The question about “Betawi”, who they are and how is the condition of “Betawi” lead to Jakarta’s government policies for cultural conservation for securing “Betawi”. The“Cagar Budaya Condet” and “Setu Babakan” is case study using in depth interview and observation for explaining and understanding the identity questions. The finding is the “Betawi” still exist and secured at Setu Babakan as “Cagar Budaya Condet” which were previously being estimated would be unsuccessful effort. Keywords: betawi, Condet cultural conservation and Setu Babakan